2008
DOI: 10.4067/s0301-732x2008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Genotipos de aislados de campo de Brucella abortus de distintas regiones geográficas de Chile

Abstract: SuMMAryBovine brucellosis is an endemic, zoonotic disease of high economic impact. The genetic identification of the prevalent Brucella abortus strains, the pathogen, is key to pursue further epidemiological strategies for disease control. The insertion sequence IS711 has been used as genetic marker to differentiate among Brucella species, members of the same specie and within the same biovar. We have analyzed the IS711-RFLP pattern for 46 B. abortus isolates, collected during the period of 1997-2005 from 16 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…Restriction analysis with XbaI showed a low variability among strains. These results are consistent with previous findings of other authors (13,22), However, the genetic homogeneity observed in most B. abortus isolates showed the need to complement this study with a methodology able to provide a higher resolution power, incorporating MLVA analysis and specifically MLVA-16 (comprising 16 loci). MLVA-16 has been shown to have good discriminatory power to determine genetic relationships among strains of the same species of Brucella (19).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Restriction analysis with XbaI showed a low variability among strains. These results are consistent with previous findings of other authors (13,22), However, the genetic homogeneity observed in most B. abortus isolates showed the need to complement this study with a methodology able to provide a higher resolution power, incorporating MLVA analysis and specifically MLVA-16 (comprising 16 loci). MLVA-16 has been shown to have good discriminatory power to determine genetic relationships among strains of the same species of Brucella (19).…”
Section: Resultssupporting
confidence: 82%
“…This finding is not surprising, since in Chile and in countries such as the United States (2), Argentina (33), and countries in Central America (23), B. abortus biovar 1 was responsible for the greatest percentages of cases of bovine brucellosis. Our results also confirmed the report of Mancilla et al on a previous study with Chilean isolates (22). Pattern A1 showed no appreciable banding differences among the 67 isolates, indicating, according to the interpretive criteria of PFGE patterns published by Tenover et al (35), that these 67 isolates were genetically indistinguishable and therefore were clonally related.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations